Identification of structural damage severity and location using piezo-ceramic transducers - Liu, Hui (2010)
The use of smart piezoceramics, more commonly Lead Zirconate Titanate (PZT) patches, in structural health monitoring (SHM) has been of much research in recent years; especially in damage detection and structure identification using electro-mechanical impedance (EMI) technique which is based on the coupling relationships between the PZT and the host structure. In SHM, damage severity identification and localization are of great importance and are the main interests. PZT transducer has shown excellent sensitivity in structural damage identification and has been successfully applied in SHM. However, systematic investigation on damage propagation and localization is still in need.